(untitled) (Medicine Today, 2025)
Introduction: Acute coronary syndrome (ACS) is a global health issue that causes premature death, disability, and rising healthcare costs. Younger people are now experiencing acute myocardial infarction (AMI), which is usually seen in older adults. Unfortunately, public awareness of AMI, its risk factors, and complications is low. Youthful coronary artery disease (CAD) prevalence and outcomes are also unknown. This study compares risk factors and in-hospital outcomes of acute ST-segment elevation myocardial infarction (STEMI) in younger (≤40 years) and older (>40 years) patients. Material and Methods: An observational, hospital-based study was conducted at the Department of Medicine, Khulna Medical College Hospital. The study included 100 consecutive patients, with 50 patients aged 40 years or younger and 50 patients older than 40 years, all diagnosed with acute STEMI. Clinical characteristics, echocardiographic findings, and in-hospital outcomes were evaluated and compared between the two age groups. Data analysis was carried out using SPSS (Statistical Package for Social Science), with statistical significance determined at a p-value ≤0.05, applying the Chi-square test for analysis. Results: The majority of patients in both age groups were male (74% in the younger group vs. 80% in the older group). The younger cohort demonstrated a significantly higher prevalence of smoking (70% vs. 54%), a positive family history of ischemic heart disease (52% vs. 32%), dyslipidemia (48% vs. 36%), and a higher body mass index (BMI). Conversely, conditions such as hypertension (14% in the younger group vs. 80% in the older group), diabetes (20% vs. 46%), and a history of angina (16% vs. 28%) were more common among older participants. Notably, the left ventricular ejection fraction (LVEF) was significantly better in the younger group (p = 0.005). Complications such as heart failure (32% vs. 16%), arrhythmias (24% vs. 8%), cardiogenic shock (18% vs. 2%), post-MI angina (12% vs. 6%), and in-hospital mortality (14% vs. 6%) were more frequent in older patients, though these differences did not reach statistical significance. Conclusion: Young patients with AMI exhibit distinct risk profiles and generally have better in-hospital outcomes compared to their older counterparts. This study underscores the importance of early intervention and control of modifiable risk factors, such as smoking, poor diet, obesity, and dyslipidemia, to mitigate the incidence of AMI in younger populations. Medicine Today 2025, Vol.37 (2): 258-262